Kerawanan Kepadatan Jentik Terhadap Risiko Penularan Penyakit DBD di Kota Padang - Rahmah, Jihad Waffiqa; Onasis, Aidil; wati, Linda; Marza, R Firwandri; Gusti, Awalia (Jurnal Kesehatan Lingkungan Mandiri, 2022)
The density of Aedes aegypti larvae is one of the risk factors for the transmission of Dengue Hemorrhagic Fever (DHF). This type of research is descriptive with a spatial approach from March to May 2022. The population in this study is 3 sub-districts with the highest population density in the Padang Pasir Public Health Center, West Padang District as many as 3,212 houses with a total of 97 houses. The results showed that ABJ in the Kelurahan in the Padang Pasir Public Health Center working area was 78.3%. Mosquito Breeding Place with a Container Index value of 17.6. The implementation of 3M activities is 78.3%. Larva density susceptibility indicates that Purus Village is an area with a density of mosquito larvae, Rimbo Kaluang Village is in the medium vulnerability category and Flamboyan Village has low vulnerability. It is hoped that the community will carry out vector control by implementing the Eradication of Mosquito Nests (PSN), the puskesmas can use GIS technology as a medium of information and developments in the transmission of DHF and cooperate with the Health Office to jointly play an active role in suppressing cases of Dengue Fever in the community.